Pocketbook and Sociotropic Economic Voting: How Does Inflation Affect Voting Decisions? - Muhammad Hassan Bin Afzal (ZBW – Leibniz Information Centre for Economics, 2024)
Economic hardships significantly affect public perception and voting intentions in general elections. The primary focus of my study is to capture the degree of influence that individual economic hardships have on their voting. I utilize the ANES 2024 Pilot Study Survey dataset and introduce a novel composite Inflation Behavior Index (IBR) that captures individuals' cumulative economic and cost of living experience. To that effect, the primary objectives of the current study are threefold: first, to develop a composite economic behavior index from available data and variables to capture the overall economic experience of U.S. individuals due to ongoing inflation; second, to examine how this economic behavior impacts political engagement and voting behavior utilizing appropriate and fitting mathematical models; and finally which specific personal experiences and perceptions about economy and cost of living likely to revoke party loyalty in upcoming U.S. presidential election. My study finds that increased personal economic struggles (pocketbook voting) due to inflation make it more likely for individuals to express an intention to vote against the Incumbent even if the Incumbent is from their self-identified political party. On the contrary, having a negative perception of the national economy (sociotropic voting) is less likely to revoke party loyalty in the upcoming General election. In simpler terms, voters are more likely to vote along party lines even if they perceive their party (the Incumbent) is not handling the economy and cost of living well. Having a higher level of Education, they are more likely to vote for the incumbents in both pocketbook and sociotropic scenarios. Therefore, the current research shows that party loyalty during general elections often persists but is expected to be undermined if the voter experiences adverse economic conditions due to inflation in the past. The findings of the current study provide tools and resources to craft agendas, policies, and strategies not only for policymakers and campaign strategists but also for the political parties to take focused and evidence-based actions to protect and ensure the economic well-being of the general population as well as increase the likelihood to perform better in elections and public opinion measures in a highly polarized political environment.
Keywords: E31; D72; 330; Economic Voting; Inflation Behavior Index (IBR); Voting Behavior; Pocketbook Voting; Elections; Sociotropic Voting